Accelerating Distributed Optimization via Over-the-Air Computing - Mitsiou, Nikos A.; Bouzinis, Pavlos S.; Diamantoulakis, Panagiotis D.; Schober, Robert; Karagiannidis, George K. (IEEE Transactions on Communications, 2023)
Distributed optimization is ubiquitous in emerging applications, such as robust sensor network control, smart grid management, machine learning, resource slicing, and localization. However, the extensive data exchange among local and central nodes may cause a severe communication bottleneck. To overcome this challenge, over-the-air computing (AirComp) is a promising medium access technology, which exploits the superposition property of the wireless multiple access channel (MAC) and offers significant bandwidth savings. In this work, we propose an AirComp framework for general distributed convex optimization problems. Specifically, a distributed primal-dual (DPD) subgradient method is utilized for the optimization procedure. Under general assumptions, we prove that DPD-AirComp can asymptotically achieve zero expected constraint violation. Therefore, DPD-AirComp ensures the feasibility of the original problem, despite the presence of channel fading and additive noise. Moreover, with proper power control of the users’ signals, the expected non-zero optimality gap can also be mitigated. Two practical applications of the proposed framework are presented, namely, smart grid management and wireless resource allocation. Finally, numerical results confirm DPD-AirComp’s excellent performance, while it is also shown that DPD-AirComp converges an order of magnitude faster compared to two digital orthogonal multiple access schemes, specifically, time-division multiple access (TDMA), and orthogonal frequency-division multiple access (OFDMA).
CRIS-Team Scopus Importer:2023-07-07
Keywords: 6G; 6G mobile communication; Convergence; distributed optimization; large-scale optimization; Linear programming; non-orthogonal multiple access; Optimization; Over-the-air computing; primal-dual; Resource management; Servers; Smart grids; subgradient method